ADAPTASI LINGUISTIK DAN SOSIAL KOMUNITAS PLURALIS DI NTB: KAJIAN ATAS SISTEM BUDAYA LOKAL DALAM RANGKA PENYIAPAN SDM PARIWISATA UNGGUL DAN INOVATIF - Syafruddin S; Kaharuddin K; I Made Sujana (Faculty of Humanities, Jember University, 2012)
Nusa Tenggara Barat (NTB), as one of the regions that is prepared to be a tourism based economic corridor development requiring competitive and innovative humanresources. By employing interview and observation methods, and the use of qualitative and quantitative data analyses, the results are: (a) there is a difference in nonverbal behavior among the plural community of NTB, although the forming element of the community is the same; (b) a number of nonverbal behaviors showing solidarity and tolerance among the pluralistic community of West Barat are reflected in ngejot, Fitrayadnya, tomb pilgrimage traditions and the formation of space expressing solidarity and tolerance in the form of Mendapa building; (c) the formation of nonverbal behavior is founded upon cultural values system assuming that human have the same origin, sharing historical similarity; (d) the nurturing of behavior reflecting solidarity and tolerance provides positive energy for creating competitive and innovative human resources.Keywords: economic corridor, pluralistic community, positive energy, solidarity, tolerance